Curiosity and the aesthetics of travel writing, 1770-1840 : 'from an antique land' - Leask, Nigel, 1958- (OUP E-Books., 2002)
The decades between 1770 and 1840 are rich in exotic accounts of the ruin-strewn landscapes of Ethiopia, Egypt, India, and Mexico. Yet it is a field which has been neglected by scholars and which - unjustifiably - remains outside the literary canon. In this pioneering book, Nigel Leask studies the Romantic obsession with these 'antique lands', drawing generously on a wide range of eighteenth- and nineteenth-century travel books, as well as on recent scholarship in literature, history, geography, and anthropology. Viewing the texts primarily as literary works rather than 'transparent' adventure stories or documentary sources, he sets out to challenge the tendency in modern academic work to overemphasize the authoritative character of colonial discourse. Instead, he addresses the relationship between narrative, aesthetics, and colonialism through the unstable discourse of antiquarianism, exploring the effects of problems of creditworthiness, and the nebulous epistemologicial claims of 'curiosity' (a leitmotif of the accounts studied here), on the contemporary status of travel writing.; Attentive to the often divergent idioms of elite and popular exoticism, Curiosity and the Aesthetics of Travel Writing plots the transformation of the travelogue through the period, as the baroque particularism of curiosity was challenged by picturesque aesthetics, systematic 'geographical narrative', and the emergence of a 'transcendental self' axiomatic to Romantic culture. In so doing it offers an important reformulation of the relations between literature, aesthetics, and empire in the late Enlightenment and Romantic periods.